Screening for genetic disorders: therapeutic abortion and IVF. Issue 1 (March 1990) - Michael, M; Buckle, S
Abstract : This paper examines a proposal to make use of IVF techniques to provide an alternative to therapeutic abortion of fetuses with genetic abnormalities. We begin by describing the proposed procedure, and then show that, considered in itself, it is morally on a par with therapeutic abortion. However, once the wider practical implications are brought into view, the proposed new procedure loses its initial appeal. The pros and cons are not sufficiently clear-cut entirely to rule out the IVF procedure, so the paper concludes by indicating some further complications which may follow, should the procedure come to be adopted.